Relationship of Estimated SHIV Acquisition Time Points During the Menstrual Cycle and Thinning of Vaginal Epithelial Layers in Pigtail Macaques. Issue 12 (December 2015) - Kersh, Ellen N.; Ritter, Jana; Butler, Katherine; Ostergaard, Sharon Dietz; Hanson, Debra; Ellis, Shanon; Zaki, Sherif; McNicholl, Janet M.
Abstract : Background: HIV acquisition in the female genital tract remains incompletely understood. Quantitative data on biological HIV risk factors, the influence of reproductive hormones, and infection risk are lacking. We evaluated vaginal epithelial thickness during the menstrual cycle in pigtail macaques ( Macaca nemestrina ). This model previously revealed increased susceptibility to vaginal infection during and after progesterone-dominated periods in the menstrual cycle. Methods: Nucleated and nonnucleated (superficial) epithelial layers were quantitated throughout the menstrual cycle of 16 macaques. We examined the relationship with previously estimated vaginal SHIVSF162P3 acquisition time points in the cycle of 43 different animals repeatedly exposed to low virus doses. Results: In the luteal phase (days 17 to cycle end), the mean vaginal epithelium thinned to 66% of mean follicular thickness (days 1–16; P = 0.007, Mann-Whitney test). Analyzing 4-day segments, the epithelium was thickest on days 9 to 12 and thinned to 31% thereof on days 29 to 32, with reductions of nucleated and nonnucleated layers to 36% and 15% of their previous thickness, respectively. The proportion of animals with estimated SHIV acquisition in each cycle segment correlated with nonnucleated layer thinning (Pearson r = 0.7, P < 0.05, linear regression analysis), but not nucleated layer thinning (Pearson r = 0.6, P = 0.15). Conclusions: These data provide a detailed picture of dynamic cycle-related changes in the vaginal epithelium of pigtail macaques. Substantial thinning occurred in the superficial, nonnucleated layer, which maintains the vaginal microbiome. The findings support vaginal tissue architecture as susceptibility factor for infection and contribute to our understanding of innate resistance to SHIV infection. Abstract : A study in an animal model for vaginal HIV infection reveals a quantitative, correlative relationship between infection risk during the menstrual cycle and thinning of the superficial vaginal epithelial layer.